An Active Functionally Graded Piezocomposite Plate Subjected to a Stochastic Pressure - PIETRZAKOWSKI, Marek (Archives of Acoustics, 2015)
In the paper the analysis of random vibration of an actively damped laminated plate with functionally graded piezoelectric actuator layers is presented. The simply supported plate is subjected to stochastic loading represented by a uniformly distributed pressure. The random input is assumed as a Gaussian stationary and ergodic process. The actuators are regarded as a multi-layer structure arranged of piezofiber composite sub-layers. The sub-layers differ each other with amount of PZT (lead-zirconate-titanate) fibers and are stacked to achieve a desired change of the PZT volume fraction through the actuator thickness. The gradation scheme of constituents and material properties are estimated by parabolic and power functions. Numerical simulations are performed to recognize the influence of the applied random excitations and the actuator properties gradations on the characteristics of the stochastic field of active plate deflection i.e. power spectral density, autocorrelation function and variance.